2006
DOI: 10.1107/s1600536806047489
|View full text |Cite
|
Sign up to set email alerts
|

(R,S)-2,2′-(Ethane-1,2-diyldiiminio)dibutan-1-ol dinitrate

Abstract: Key indicatorsSingle-crystal X-ray study T = 113 K Mean (C-C) = 0.003 Å R factor = 0.060 wR factor = 0.158 Data-to-parameter ratio = 17.9For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…1). Bond lengths and angles are normal (Allen et al, 1987) and similar to those found in the neutral (R,S)molecule (Bai, Zhang, Qin et al, 2006), in (R,S)-ethambutol dinitrate (Bai, Zhang, Simpson et al, 2006) and in comparable aminoethyl sulfate compounds (Post, 1978;Munns et al, 1981). The O1-C1-C2-N1 torsion angle of 63.7 (2) indicates a gauche conformation, as found in similar aminoethylsulfate derivatives (Post, 1978;Munns et al, 1981).…”
Section: Commentsupporting
confidence: 62%
“…1). Bond lengths and angles are normal (Allen et al, 1987) and similar to those found in the neutral (R,S)molecule (Bai, Zhang, Qin et al, 2006), in (R,S)-ethambutol dinitrate (Bai, Zhang, Simpson et al, 2006) and in comparable aminoethyl sulfate compounds (Post, 1978;Munns et al, 1981). The O1-C1-C2-N1 torsion angle of 63.7 (2) indicates a gauche conformation, as found in similar aminoethylsulfate derivatives (Post, 1978;Munns et al, 1981).…”
Section: Commentsupporting
confidence: 62%
“…In order to overcome the undesirable effects of ( S , S )-EDH, an extensive amount of studies have been emerged in the last few years, many of them dealing with the development of multicomponent crystal forms of this drug. Recently, Nangia et al have been prepared and characterized five salts (sulfate, dimesylate, ditosylate, dibesylate, and fumarate) and two ionic liquids (dibenzoate and adipate), but all of them were found to be hygroscopic . For this reason, herein we report a screen of ETB with a series of carboxylic/dicarboxylic acids, trichloroacetic, maleic, oxalic, and terephthalic acids.…”
Section: Introductionmentioning
confidence: 98%